Hyperactivity and impulsivity in adult attention-deficit/hyperactivity disorder is related to glutamatergic dysfunction in the anterior cingulate cortex. (3rd October 2018) - Bauer, Jochen; Werner, Anne; Kohl, Waldemar; Kugel, Harald; Shushakova, Anna; Pedersen, Anya; Ohrmann, Patricia
Abstract: Objectives: Attention-deficit/hyperactivity disorder (ADHD) is closely linked to the dysregulation of dopaminergic and noradrenergic neurotransmission in the fronto-striatal neural network, including the anterior cingulate cortex (ACC) and the dorsolateral prefrontal cortex (DLPFC). Additionally, increasing evidence supports the involvement of the glutamatergic system in the pathophysiology of ADHD. Impulsivity, a core symptom in patients with ADHD, has been repeatedly associated with glutamatergic neurotransmission, and pharmacological treatment of ADHD has been shown to reduce glutamate levels in the prefrontal cortex. Methods: We investigated glutamate levels in the ACC and the DLPFC in 30 adults with ADHD and 30 healthy controls using single-voxel proton magnetic resonance spectroscopy on a 3T scanner. Results: The ADHD group showed a significant increase in glutamate in the ACC compared to controls, no significant differences in metabolites were observed in the DLPFC. Overall, glutamate levels in the ACC were positively correlated with ADHD symptomatology, especially hyperactivity and impulsivity symptoms. Conclusions: Increased levels of glutamate in the ACC, which were positively correlated with hyperactivity and impulsivity, support the hypothesis that dysfunctional glutamatergic neurotransmission is at least partially responsible for ADHD symptomatology. Modulation of glutamatergic neurotransmission might therefore be a promising avenue for future pharmacological interventions.